Utility of copeptin in predicting non-pathological postoperative polyuria in patients affected by acromegaly undergoing pituitary neurosurgery - Varaldo, Emanuele; Prencipe, Nunzia; Berton, Alessandro Maria; Aversa, Luigi Simone; Bioletto, Fabio; De Marco, Raffaele; Gasco, Valentina; Zenga, Francesco; Grottoli, Silvia (Pituitary, 2024)
Purpose Copeptin efficiently predicts post-neurosurgical central diabetes insipidus (CDI) in patients with hypothalamic-pituitary lesions, but its role in characterizing changes in diuresis in individuals with acromegaly undergoing neurosurgery remains unexplored. Our study aimed to assess changes in postoperative fluid balance in acromegaly patients and correlate them with both copeptin and growth hormone (GH) levels. Methods This was a secondary analysis of a prospective study involving 15 acromegaly patients undergoing endoscopic endonasal resection at our University Hospital. Fluid balance was assessed daily, and copeptin and GH levels were evaluated preoperatively (T0), and serially on the morning of the first (T2) and second (T3) postoperative day, with an additional measurement of copeptin one hour post-extubation (T1). Patients with pre-existing or post-neurosurgical CDI were excluded from the analysis. Results Most patients (11/15) exhibited a negative fluid balance on the second postoperative day, with 4 developing polyuria. Postoperative GH levels did not differ significantly between polyuric and non-polyuric patients, but GH measured at T2 correlated significantly with negative total balance ( r = -0.519, p = 0.048). Copeptin levels at T1 were significantly higher in those who developed polyuria ( p = 0.013), and a copeptin value > 39.9 pmol/L at T1 showed excellent ability (Sensitivity 100%, Specificity 90.9%, p < 0.001) in predicting postoperative polyuria. Additionally, polyuric patients exhibited a higher T1 / T3 copeptin ratio ( p = 0.013) and a negative fluid balance was associated with the remission of acromegaly at 12 months ( p = 0.046). Conclusion The early assessment of copeptin, in addition to facilitating the rapid identification of individuals at increased risk of developing CDI, could also allow the recognition of subjects with a tendency towards non-pathological polyuria in the postoperative setting, at least in individuals affected by acromegaly.